1982
DOI: 10.2527/jas1982.544796x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Glycogen Levels in Dams and Fetuses as Affected by Fasting and Refeeding Pregnant Sows1

Abstract: Nineteen Landrace sows mated to Landrace boars were randomly assigned, on d 91 of pregnancy, to three groups: (1) control (six sows)--fed standard 13% protein corn-soybean meal gestation diet at 1.82 kg/d to d 112 of pregnancy; (2) 4-d fast (seven sows)--fed standard gestation diet to d 94 of pregnancy, fasted from d 95 to 98 of pregnancy and then refed a semipurified fat-free diet ad libitum until d 112 of pregnancy, and (3) 8-d fast (six sows)--treated the same as groups 2, except that the fast began on d 91… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…These results support the validity of the Iberian pig as a robust, amenable and reliable translational model for studies on nutrition-associated diseases. In the present study, the effects of prenatal programming were found after feeding the Iberian sows with diets more moderate than reported in other swine models [20-22], like we have previously found in dietary treatments for inducing obesity and associated disorders at juvenile and adult stages [4,5]. These unique features can be related to the background of exposure to harsh environments and food scarcity for generations of the Iberian pig.…”
Section: Discussionsupporting
confidence: 71%
“…These results support the validity of the Iberian pig as a robust, amenable and reliable translational model for studies on nutrition-associated diseases. In the present study, the effects of prenatal programming were found after feeding the Iberian sows with diets more moderate than reported in other swine models [20-22], like we have previously found in dietary treatments for inducing obesity and associated disorders at juvenile and adult stages [4,5]. These unique features can be related to the background of exposure to harsh environments and food scarcity for generations of the Iberian pig.…”
Section: Discussionsupporting
confidence: 71%
“…In support of this. Yen et al (1982) demonstrated that fasting late pregnant sows for 4 or 8 d (ending d 98 of gestation) did not reduce fetal glycogen pools.…”
Section: Discussionmentioning
confidence: 97%
“…Fetal tissue glycogen stores and plasma glucose are generally considered to be refractory to maternal energy intake in swine (28)(29)(30); induction of maternal alloxan diabetes does increase fetal glycogen reserves (3 1). The higher plasma glucose is suggestive of a diabetogenic effect of the high-protein-lowcarbohydrate diet.…”
Section: Discussionmentioning
confidence: 99%